Innovation and Development of a Video-Assisted Tutorial for Book Writing to Support Reference Book Writing Skills in PPG Students - Evania Yafie; Muhammad Jauharul Fuady; Muhammad Alfan; Anik Nur Handayani; Suziyani Mohamed; Suti Mega Nur Azizah (AL-ISHLAH: Jurnal Pendidikan, 2025)
Writing skills are essential for Teacher Professional Education (PPG) students, particularly in producing well-structured and ethical reference books. However, many students struggle due to limited experience and the absence of systematic guidance. This study aims to develop and evaluate a Video-Assisted Tutorial Book Writing (VABTBW) model to support the improvement of reference book writing skills in PPG students. This research employed a Research and Development (RD) design using the ADDIE model (Analysis, Design, Development, Implementation, Evaluation). The development process involved expert validation from three domains—material, media, and instructional design—and a practicality test involving PPG students. Data were analyzed using descriptive percentage analysis. Expert validation results indicated that the VABTBW model is highly valid, with average scores of 90% (material experts), 92% (media experts), and 93% (instructional design experts). The practicality test showed a score of 90%, suggesting that the model is very practical for use in learning environments. The VABTBW model effectively enhances students’ conceptual understanding and practical competence in writing reference books. Its integration into PPG programs supports not only academic writing skills but also digital literacy, aligning with current educational demands. This innovation promotes active learning, increases writing productivity, and prepares future educators to become competent and digitally capable professionals.